INTERVENTIONS IN PARENTING TO PROMOTE CHILD MENTAL HEALTH MEDIATED BY LIBRARY THERAPY - Frota, Sarah Donato de Moura (2023)
Interventions in parenting for the promotion of children's mental health are effective in enabling parents to deal with their children's behavioral challenges. The objective of the study was to understand the meanings of parenting from the perspective of parents in mental health care in early childhood and to propose interventions mediated by Bibliotherapy. This is a research with a mixed approach carried out through semi-structured interviews and bibliotherapeutic focus groups. It was found that the ability to change the parents' mentality and behavior has implications for the child's development, based on the understanding of the meanings attributed by them to their children's behavior. The practice of metaparenting, a construct that means improving parental competence and reducing stress and adopting positive educational practices, is effective in the exercise of parenting that promotes mental health. And, it favors continuous relationships between parents and children and long-lasting social interactions, providing opportunities for the psychic, cognitive, behavioral and emotional development of their children. Parents who have access to interventions in parenting that encourage self-knowledge (thoughts with awareness) and learning (social cognition) can generate significant transformations caused by changing behavior and self-care, modifying the environment and social context in which the child is insert.